Salak Coffee: Revolusi Ekonomi Kreatif dari Limbah Salak Enrekang - Machmud, Mulyana; Syahril, Muh. Akbar Fhad; Nur Qadri, Sri (Celebes Journal of Community Services, 2024)
This service activity aims to overcome the problem of managing waste from salak bark and seeds in Pekalobean Village, Enrekang Regency, which has not been utilized optimally so far. By utilizing local potential, this activity develops coffee products from the waste as an effort to empower the community's creative economy. The methods used include the collection of qualitative and quantitative data, as well as the implementation of training for farmer groups in processing waste into coffee products. The results of the service activities show that the salak waste processing process can produce coffee that has a unique taste and is well received by the community. In addition, the training carried out increases knowledge and skills in processing waste, which has the potential to increase their income. Thus, these innovations not only add value to waste, but also contribute to the improvement of the local economy and environmental sustainability.